Mengelola Pekerja Pengetahuan - Raharso, Sri (Jurnal Administrasi Bisnis, 2011)
A growing belief has emerged that effectively managing knowledge can enhance per-formance. Prosperity now depends less on access to physical resources and more andmore on the ability to create economically useful new ideas. Knowledge is a centralfeature of post-industrial societies. The significance of knowledge as a vital resourcefor the worldâs economies has been underlined; it forms the basis for innovation andeconomic success. Knowledge has become the most important basis for competition.More organizations core competencies will center around managing knowledge andknowledge worker. Knowledge management is the strategy for creating, accessingand supporting this vital resource. The task of knowledge worker is acquisition,creation, packaging, or application of knowledge. However, the nature of knowledgework is different from administrative and operational work and that the people whoperform it resist structured approaches. Hence, a viable approach critically neededfor improving knowledge work.Keywords: knowledge management, knowledge work, knowledge worker